OPTIMALISASI SUMBER DAYA MANUSIA DALAM PENERAPAN E-GOVERNMENT DI DESA WANTILAN - Tinda Irawaty; Widuri Wulandari; Titin Rohayatin; Noer Apptika Fujilestar (Lembaga Penelitian dan Pengabdian Masyarakat, 2023)
Community service carried out aims to improve the knowledge, abilities, and skills of village officials in e-government in administering government at the village level. Human Resource is an important factor in an organization. With various forms and objectives, the organization is made based on various visions for the benefit of the organization and in carrying out its mission it is managed and managed by employees. Implementation of village-level e-government as a form of village digitization so that villages become smart villages. This activity is carried out in three stages, namely the preparation stage in the form of socializing activities with village officials, the implementation stage is carried out by delivering material, focus group discussions (FGD) and training or tutors, and the last stage is an evaluation by asking participants about knowledge related to e-commerce. government. The results show that participants understand e-government but still need further guidance. Keywords: E-government, Human Resources, Village Government